Faktor Risiko yang Menyebabkan Pembengkakan Biaya di Jaringan Jalan - Amizar Amizar; Bambang Priyambodo (Universitas Batanghari Jambi, 2023)
Cost overruns are a common phenomenon observed in construction projects around the world. This is one of the biggest challenges experienced in the construction industry which leads to an over budget, and directly affects the gross domestic product (GDP) of the country. This study aims to identify factors that significantly contribute to cost overruns for road network projects in Egypt during the implementation phase. The survey was conducted to determine the most critical factors affecting cost overrun for road network development projects. The results showed that the main factors causing cost overruns were inaccurate cost estimates, design modifications, quantity changes, order variations, political interference, inflation, specification changes, and scope of work changes.